Quantization of the superstring with manifest U(5) super-Poincaré invariance - Berkovits, Nathan [UNESP] (Elsevier, 1999)
The superstring is quantized in a manner which manifestly preserves a U(5) subgroup of the (Wick-rotated) ten-dimensional super-Poincaré invariance. This description of the superstring contains critical N = 2 worldsheet superconformal invariance and is a natural covariantization of the U(4)-invariant light-cone Green-Schwarz description. © 1999 Published by Elsevier Science B.V. All rights reserved.